Analyzing Vitamin C Levels in Leersia hexandra Extract through Solvent Variations - Annisa, Novia; Violita; Irma Leilani Eka Putri; Siska Alicia Farma (Journal of Biotropical Research and Nature Technology, 2023)
Various food sources and herbal plants are rich in Vitamin C, a crucial antioxidant. One such plant is Banto grass, which belongs to the Poaceae family and is commonly used as an herbal drink in many communities. It contains active compounds known for their healing and disease-prevention properties. This study aimed to evaluate the levels of vitamin C in Banto grass extract using different solvents. The research followed a descriptive approach and used UV-Vis Spectrophotometry as the analytical method. The findings showed that the vitamin C content varied significantly in Banto grass extracts prepared with distilled water, ethanol, and methanol solvents. The extract prepared with methanol had the highest vitamin C content of 4,030 ppm, which was more than the eco-enzyme water extract that contained 4,030 ppm of vitamin C. However, the extracts prepared with distilled water and ethanol solvents had lower vitamin C levels of 2,507 ppm and 3,687 ppm, respectively. This research highlights the potential of Banto grass as a rich source of vitamin C, which is essential for collagen formation, wound healing, and antioxidant activity, leading to faster wound healing and optimal tissue repair.